Successful rescue of PD-1 inhibitor-induced TEN by vincristine combination therapy: a case report and literature review - Huang, Hui-Yi; Liu, Jia-Qi; Zeng, Yun-Yun; Huang, Zhi-Hao; Su, Shan (Frontiers in Oncology, 2025)
With the growing use of immune checkpoint inhibitors (ICIs) in the management of various solid malignancies, immune-related adverse events (irAEs) are increasingly recognized. Toxic epidermal necrolysis (TEN), though rare, represents a severe and potentially fatal cutaneous irAE with a high mortality rate. Owing to its low incidence and limited clinical data, a standardized treatment approach for ICI-induced TEN has not been established. We present a patient who developed TEN following the administration of a programmed cell death-1 inhibitor. The patient was successfully managed with a combination of vincristine, intravenous immunoglobulin, and glucocorticoids at the Department of Oncology, Guangzhou Chest Hospital.